2007
DOI: 10.1103/physrevb.76.045111
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar field-effect transistor characteristics of (BEDT-TTF)(TCNQ) crystals and metal-like conduction induced by a gate electric field

Abstract: Ambipolar carrier conduction has been observed in a metal-insulator-semiconductor field-effect transistor made using ͑BEDT-TTF͒͑TCNQ͒ crystals. The temperature dependence of the source current with the applied positive gate voltage exhibits metal-like behavior at around room temperature. The metal-like conduction transforms into thermal-activation-type behavior below 240 K. The I S -V DS curve for an applied gate voltage of 80 V exhibited a corresponding change in the curvature below 240 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…Field-effect doping in such materials is of particular interest in condensed matter physics. Ambipolar-type field-effect characteristics are observed in SC-OFETs using Mott insulators of (BEDT-TTF)(F 2 TCNQ) [BEDT-TTF ( bis(ethylenedithio)tetrathiafulvalene)] [14], and of (BEDT-TTF)(TCNQ) [75] as channel single crystals. The unique ambipolar operations may be associated with the effect of carrier accumulation at the Schottky barriers in the source/drain contacts with Mott insulators [76,77].…”
Section: Sc-ofets Of Charge-transfer Compoundsmentioning
confidence: 94%
“…Field-effect doping in such materials is of particular interest in condensed matter physics. Ambipolar-type field-effect characteristics are observed in SC-OFETs using Mott insulators of (BEDT-TTF)(F 2 TCNQ) [BEDT-TTF ( bis(ethylenedithio)tetrathiafulvalene)] [14], and of (BEDT-TTF)(TCNQ) [75] as channel single crystals. The unique ambipolar operations may be associated with the effect of carrier accumulation at the Schottky barriers in the source/drain contacts with Mott insulators [76,77].…”
Section: Sc-ofets Of Charge-transfer Compoundsmentioning
confidence: 94%
“…Molecular wires of (TTF)(TCNQ) formed under electric fields are investigated, and electron-like transport has been observed, which has been also ascribed to the TCNQ-rich situation. 54 (BEDT-TTF)(TCNQ) behaves as a Mott insulator below the metalinsulator transition temperature at 330 K. Ambipolar transport is observed, and the mobility increases down to 240 K. 55 Additional dielectric anomaly at 285 K has been suggested. 55 Single-crystal transistors of (BEDT-TTF)-(F 2 TCNQ) are also investigated at low temperatures, and ambipolar transport has been observed.…”
Section: ç Ofets Based On Charge-transfer Complexesmentioning
confidence: 99%
“…54 (BEDT-TTF)(TCNQ) behaves as a Mott insulator below the metalinsulator transition temperature at 330 K. Ambipolar transport is observed, and the mobility increases down to 240 K. 55 Additional dielectric anomaly at 285 K has been suggested. 55 Single-crystal transistors of (BEDT-TTF)-(F 2 TCNQ) are also investigated at low temperatures, and ambipolar transport has been observed. 56 ¬-(BEDT-TTF) 2 -Cu[N(CN) 2 ]Br is an organic superconductor with the transition temperature of 11.8 K but located on the border of the Mott insulator.…”
Section: ç Ofets Based On Charge-transfer Complexesmentioning
confidence: 99%
“…The monolayer thickness was fitted at about 2.1 nm and separated into a 0.7 nm alkyl-spacer and a 1.4 nm TTF core with clearly different density. An additional layer of about 0.81 nm with a very low density (about 0.24 g/cm 3 ) was calculated to exist on the surface of monolayer. The molecular weight for the EDT-DMT-TTF core and C 9 alkyl chain without phosphonic acid is 385 and 126, respectively, giving a weight ratio of 3.06.…”
Section: Methodsmentioning
confidence: 99%
“…3 (BEDT-TTF = bis(ethylenedithio)tetrathiafulvalene; TCNQ = tetracyanoquinodimethane) Hasegawa T. et al also reported a single-crystal-based Mott FET with a similar compound. 4 Although their device performance was moderate, a fundamental operation was confirmed by these experiments.…”
Section: Introductionmentioning
confidence: 99%